Instructions Concerning Alien Enemy Travel - United States. District Attorney (New York : Southern District) (1942)
Application and instructions for immigrants from German or Japan to request the ability to travel within the United States. Form has been completed by Max Bredig (1902-1977).
Keywords: Bredig, Max Albert, 1902-1977; Noncitizens; World War (1939-1945)